Effects of Personality on Social Status A Study on Perceived Social Dominance Among Adolescent Single Sex Social Groups - Moreno, Karol Matthew B. (Animo Repository, 2021)
This study intends to ascertain the relationship between personality traits and perceived social dominance in a peer group setting among Senior High School Students. There are many factors that affect the perceived social dominance of individuals, and so the research aimed to solve which factors these are among the current generation of senior high students. A total of 46 participants answered a google forms survey. It was found that the personalities all had similar measures, such as agreeableness and openness, and conscientiousness and neuroticism. Extroversion gave the most interesting results, with a half and half split for introverted(f=24, %=52.2%) and extroverted(f=22, %=47.8%). It was found that communication (m=3.24, sd= 0.85) and to be there when a friend is needed(m=3.15, sd=0.87) are the most important domains to peer relationship. Interestingly, there is no statistical relationship between age (x2=4.67, p=0.197), and gender(x2=0.186, p=0.666) with perceived social dominance. However statistical relationship is established between extraversion measure (x2=8.9, p=0.003) and quality of peer relationship (x2=4.63, p=0.031) and perceived dominance. The presented evidence warrants assumption that certain personality traits influence social dominance, and it is not related to age, gender, or quality of peer relationships.